2021
DOI: 10.18295/squmj.8.2021.121
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Perceptions and Body Image Dissatisfaction among Medical Students in Oman

Abstract: Objectives: To study body image perceptions and body image dissatisfaction, and their relationship with Body Mass Index (BMI) among medical students in Oman. Methods: A cross-sectional study was conducted among students of a private medical college in Oman. Data (including self-reported weight and height) was collected through a questionnaire-based survey. Body image perception and satisfaction were assessed using Stunkard Figure Rating Scale (FRS).. Students' responses were collected, analyzed, and interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…The primary reason for this dissatisfaction was excess weight, notably high among the French participants. These data reflect the common concern of weight management and body image among young adults, as explored in the study by Divecha et al [ 43 ]. Despite this dissatisfaction, results indicate a low level of physical exercise among participants, with around one-fifth reporting never engaging in physical activity and about one-third doing it only once a week.…”
Section: Discussionsupporting
confidence: 80%
“…The primary reason for this dissatisfaction was excess weight, notably high among the French participants. These data reflect the common concern of weight management and body image among young adults, as explored in the study by Divecha et al [ 43 ]. Despite this dissatisfaction, results indicate a low level of physical exercise among participants, with around one-fifth reporting never engaging in physical activity and about one-third doing it only once a week.…”
Section: Discussionsupporting
confidence: 80%
“…The results showed that participants self-reported inadequate knowledge regarding appearance-specific care and wanted access to an accredited course [ 60 ]. Additionally, multiple studies indicate that high degree of body image dissatisfaction and inaccurate perceptions exists among students within health-related fields, such as medical students [ 61 , 62 ], nursing students [ 63 ], and pharmacy students [ 64 ]. Therefore, future research should not only further explore whether DIF exists between educational level but also between participants’ study majors (e.g., health-related vs. non-health-related).…”
Section: Discussionmentioning
confidence: 99%
“…It seems especially important to monitor dissatisfaction and disturbed body perception among students who will be professionals responsible for the promotion and enhancement of public health in the future. This applies, for example, to students of physical education, nursing, physiotherapy, medicine [30].…”
Section: Discussionmentioning
confidence: 99%